TRADISI JAMAAH HAJI ORANG BUGIS SEPULANG DARI TANAH SUCI MEKAH (PERSPEKTIF KOMPASTV MAKASSAR) - Suf Kasman (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Once a year, Muslims of every ethnic group, color, social status, and culture gather together in Mecca and stand before the Kaaba praising Allah together. a religious tradition that brings millions of devout Muslims to the holy city of Mecca, Saudi Arabia.Muslims, especially Bugis People, At the end of the hajj, pilgrims return home and are often given the honorific “hajji,” meaning one who has performed the hajj.The research object is the local daily KOMPASTV in Makassar, KOMPAS TV in Makassar as a sample. Currently, technology has gained increasing attention as a major means to provide servicesThe research was aimed to analyze the tradition of hajj Bugis people pilgrimage from Mecca Bugis Family members often prepare a celebration to welcome pilgrims home and congratulate them on completing the journey. It is recommended to be humble in such gatherings and to ask the ones returning from Hajj to pray for your forgiveness, as they are in a strong position to do so. Once a year, Muslims of every ethnic group, colour, social status, and culture gather together in Mecca and stand before the Kaaba praising Allah together. a religious tradition that brings millions of devout Muslims to the holy city of Mecca, Saudi Arabia.Muslims, especially Bugis People, At the end of the hajj, pilgrims return home and are often given the honorific “hajji,” meaning one who has performed the hajj.The reaserach object is the local daily KOMPASTV in Makassar, KOMPASTV in Makassar as a sample. Currently, technology has gained increasing attention as a major means to provide servicesResearch was aimed to analyze tradition of hajj Bugis people pilgrimage from MeccaBugis Family members often prepare a celebration to welcome pilgrims home and congratulate them on completing the journey. It is recommended to be humble in such gatherings and to ask the ones returning from Hajj to pray for your forgiveness, as they are in a strong position to do so.